2021
DOI: 10.1039/d1cc01120k
|View full text |Cite
|
Sign up to set email alerts
|

Nonblinking carbon dots for imaging and tracking receptors on a live cell membrane

Abstract: Blinking occurs with nearly all fluorophores including organic dyes, fluorescent proteins, semiconductor quantum dots and carbon dots (CDs). We developed non-blinking and photoresistant fluorescent CDs by introducing multiple aromatic domains...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…[6][7][8][9][10] Due to their unique combination of multiple appealing properties (photoluminescence, biocompatibility, and inexpensive fabrication), C-dots have been widely employed in biological labeling/sensing, biomedicine, photocatalysis, optoelectronic devices, and so on. [11][12][13][14][15][16][17][18] clarify their structure-property relationships, including photoluminescence processes.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Due to their unique combination of multiple appealing properties (photoluminescence, biocompatibility, and inexpensive fabrication), C-dots have been widely employed in biological labeling/sensing, biomedicine, photocatalysis, optoelectronic devices, and so on. [11][12][13][14][15][16][17][18] clarify their structure-property relationships, including photoluminescence processes.…”
Section: Introductionmentioning
confidence: 99%
“…Chemokine receptors CXCR4 and CCR3 tagged with EGFP were found to dimerize on T-REx-293 cell membranes in our previous work. In this study, we further optimized the experimental details and improved the imaging quality to investigate the oligomeric status of CCR5 receptors. The EGFP tag was replaced by mNeonGreen since it is monomeric, about 3-fold brighter, and 3-fold shorter maturation time than that of EGFP. , T-REx-293 cells were replaced by CHO-K1 (hereinafter referred to as CHO) cells as we found that CHO cells have higher adherent growth ability and are more suitable for TIRFM imaging.…”
mentioning
confidence: 99%
“…3 Currently, extensive attention has been paid to CDs owing to their several advantages, such as abundant carbon source, low cost, excellent biocompatibility, 4,5 water solubility, [6][7][8] and fascinating fluorescent properties. [9][10][11] Additionally, CDs are widely applied for bioimaging, [12][13][14][15] sensing, [16][17][18][19] lubrication, 20 solar cells, [21][22][23] catalysis, [24][25][26][27] batteries, 28,29 etc. Various carbon materials can be adopted to prepare CDs, such as graphite, 30 graphene, 31 glucose, 32 carbon nanotubes and carbon fibers, 33,34 and citric acid, 35,36 and even biomass like the leaves 37,38 and fruits of plants.…”
Section: Introductionmentioning
confidence: 99%